2013
DOI: 10.1007/s11661-013-2009-z
|View full text |Cite
|
Sign up to set email alerts
|

Distortion in a 7xxx Aluminum Alloy during Liquid Phase Sintering

Abstract: The distortion in a sintered 7xxx aluminum alloy, Al-7Zn-2.5Mg-1Cu (wt. pct), has been investigated by sintering three rectangular bars in each batch at 893 K (620°C) for 0 to 40 minutes in nitrogen, followed by air or furnace cooling. They were placed parallel to each other, equally spaced apart at 2 mm, with their long axes being perpendicular to the incoming nitrogen flow. Pore evolution in each sample during isothermal sintering was examined metallographically. The compositional changes across sample mid-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…5 Assuming that the oxygen concentration is homogeneous in the incoming nitrogen gas, the convective oxygen flux (J) depends simply on the oxygen concentration (C) and flow velocity (v): J5CNv. Thus, the oxygen flux is proportional to the flow velocity.…”
Section: Discussion Distortionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Assuming that the oxygen concentration is homogeneous in the incoming nitrogen gas, the convective oxygen flux (J) depends simply on the oxygen concentration (C) and flow velocity (v): J5CNv. Thus, the oxygen flux is proportional to the flow velocity.…”
Section: Discussion Distortionmentioning
confidence: 99%
“…17 Earlier work has shown that the distortion in the as sintered Al-7Zn-2.5Mg-1Cu samples predominantly occurs during isothermal sintering at 620uC. 5 Hence, the 3D CFD modelling focused on the isothermal stage. It should be noted that powder compacts have lower thermal conductivity than fully dense material.…”
Section: Cfd Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, besides chemical and physical interactions with aluminium [12], the removal of the lubricant's vapour and volatile products of its decomposition seems to be the main role of the flowing nitrogen sintering atmosphere in the manufacturing of sintered parts made of aluminium alloys. Yuan et al demonstrated [13] the influence of the nitrogen gas flow pattern on the sintering of a 7xxx aluminium alloy produced from elemental powders with compacts' distortion. In particular, they analysed the effect of the sample position in the furnace on its distortion.…”
Section: Introductionmentioning
confidence: 99%
“…This step (termed "sizing") is typically completed at room temperature utilizing rigid tooling and press technology comparable to that used during powder compaction. While studies have looked into the mechanisms of sintering-induced distortion [11][12][13], there exists a clear void in the open literature on the effects of the actual sizing operation itself. Furthermore, the incorporation of post-sinter sizing and heat-treatment processes introduces the unique challenge of whether to apply sizing before, during, or after the heat-treatment cycle.…”
Section: Introductionmentioning
confidence: 99%